MANAGEMENT TECHNIQUES FOR THE RECOVERY OF DEGRADED BRACHIARIA PASTURES (Brachiaria decumbens Stapf cv. Basilisk) - Kondo Santini, Jose Mateus [UNESP]; Buzetti, Salatier [UNESP]; Galindo, Fernando Shintate [UNESP]; Dupas, Elisangela [UNESP]; Coaguila, Daniel Noe [UNESP] (Inst Zootecnia, 2015)
The supply of nutrients is an important factor for pasture nutrition, increasing biomass productivity and improving forage quality. The correct application of fertilizers to degraded pasture areas promotes the development of forage plants and the consequent reestablishment of the culture by providing nutrients to meet the metabolic requirements of the plant. The objective of this study was to evaluate the effect of combinations of liming, fertilization and overseeding on the recovery of Brachiaria grass (Brachiaria decumbens Stapf cv. Basilisk) in an advanced stage of degradation. A randomized block design consisting of six treatments and four repetitions was used. The following treatments were evaluated: control; liming; liming + NPK; liming + NPK + FTE (fritted trace elements); liming + NPK + Zn, and liming + NPK + FTE + overseeding of Marandu grass (Brachiaria brizantha cv. Marandu). The combinations of liming and fertilization did not influence the chemical composition of the pasture. Liming + NPK + FTE + overseeding was superior in terms of biomass productivity when compared to the control treatment and did not differ from the other treatments. The mean concentrations of N, P, Ca and Mg in the aerial part of Brachiaria grass were not influenced by the fertilization combinations. Evaluation of total N export by the plant revealed a significant effect, with the liming + NPK + FTE + overseeding treatment being superior (75.76%) to the control and liming treatments, which did not differ from one another. The use of liming and fertilization, in a single application, is not sufficient to completely recover or to increase the productivity and quality of Brachiaria grass. Overseeding of Marandu grass on Brachiaria pastures, in conjunction with liming and fertilization, is a good alternative to increase the productivity and to improve the quality of pastures in an advanced stage of degradation.
Keywords: pasture fertilization; plant nutrition; overseeding